Pengembangan Sistem Informasi Pencatatan Nilai dan Presensi berbasis Website pada Rumah Sakit Umum Daerah Kanjuruhan Kabupaten Malang - Moh. Izza Auladina Latansya; Issa Arwani; Dwija Wisnu Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Kanjuruhan Regional General Hospital, Malang Regency is a regional hospital that has an important role in Malang Regency and the surrounding area. Since 2020, Kanjuruhan Hospital, Malang Regency has officially become a teaching and research hospital referring to the Decree of the Minister of Health of the Republic of Indonesia in 2020. Kanjuruhan Regional Hospital, Malang Regency is a reference for students who are carrying out educational activities, especially for medical students who are in the medical professional education phase. However, in its implementation, medical professional education activities experienced obstacles, including recording student scores that were still manual, inefficient documentation of student data, and an absenteeism recap process that was not recorded properly, making academic activities run less optimally. Based on the problems that exist, a website-based student score recording and attendance information systems was created that can facilitate academic activities such as recapitulation and recording of grades, and accurate attendance recaps. The student score recording and attendance information systems is built using a waterfall approach. The needs analysis was obtained after conducting interviews and observations at the Education and Research (Diklit) as the person in charge of student academic activities. From the results of the analysis carried out through observation and interviews, 20 functional needs and 2 non-functional needs were obtained. The system implementation process is carried out using the Laravel framework, the MySQL database, as well as the PHP programming language. The score recording and attendance information systems that has been built will then be tested using usability testing to measure the level of user acceptance of features, the flow of activities on the system, and the display of the student score recording and attendance information systems. The results of the usability test show a number of 85.5 which indicates that users can receive information systems and the features in them.